mTOR Signaling, Translational Control, and the Circadian Clock - Cao, Ruifeng (Frontiers in Genetics, 2018)
Almost all cellular processes are regulated by the approximately 24 h rhythms that are endogenously driven by the circadian clock. mRNA translation, as the most energy consuming step in gene expression, is temporally controlled by circadian rhythms. Recent research has uncovered key mechanisms of translational control that are orchestrated by circadian rhythmicity and in turn feed back to the clock machinery to maintain robustness and accuracy of circadian timekeeping. Here I review recent progress in our understanding of translation control mechanisms in the circadian clock, focusing on a role for the mammalian/mechanistic target of rapamycin (mTOR) signaling pathway in modulating entrainment, synchronization and autonomous oscillation of circadian clocks. I also discuss the relevance of circadian mTOR functions in disease.